2012
DOI: 10.1371/journal.pone.0031781
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Ecology and Evolutionary Success of Crocodilians Revealed through Bite-Force and Tooth-Pressure Experimentation

Abstract: BackgroundCrocodilians have dominated predatory niches at the water-land interface for over 85 million years. Like their ancestors, living species show substantial variation in their jaw proportions, dental form and body size. These differences are often assumed to reflect anatomical specialization related to feeding and niche occupation, but quantified data are scant. How these factors relate to biomechanical performance during feeding and their relevance to crocodilian evolutionary success are not known.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
262
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 163 publications
(278 citation statements)
references
References 41 publications
12
262
3
1
Order By: Relevance
“…Erickson and colleagues conducted a series of studies that measured bite force in a growth series of American alligator (Erickson et al, 2003;Gignac and Erickson, 2015) and extant crocodylian species (Erickson et al, 2012(Erickson et al, , 2014. Across a size range of 31.5 to 405.5 cm total length, these studies found a positive allometric relationship (b) between maximum bite force and a variety of body size proxies, such as total length (b=2.62; isometry=2), snout-vent length (b=2.59; isometry=2), mass (b=0.79; isometry=0.667) and head length (b=2.75; isometry=2).…”
Section: Introductionmentioning
confidence: 99%
“…Erickson and colleagues conducted a series of studies that measured bite force in a growth series of American alligator (Erickson et al, 2003;Gignac and Erickson, 2015) and extant crocodylian species (Erickson et al, 2012(Erickson et al, , 2014. Across a size range of 31.5 to 405.5 cm total length, these studies found a positive allometric relationship (b) between maximum bite force and a variety of body size proxies, such as total length (b=2.62; isometry=2), snout-vent length (b=2.59; isometry=2), mass (b=0.79; isometry=0.667) and head length (b=2.75; isometry=2).…”
Section: Introductionmentioning
confidence: 99%
“…The Saltwater Crocodile is the largest living reptile on Earth; it can grow up to 6-7 m (Webb et al 1978;Whitaker & Whitaker 2008;Erickson et al 2012). Like other crocodilians it is an opportunistic feeder, using active hunting or 'sit and wait' strategies (Cooper & Jenkins 1993), and the frequency of different prey items varies significantly with habitat and body size (Taylor 1979;Webb & Manolis 1989).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ISOs of crocodylids are found across their entire body and are thus poorly situated for receiving surface waves. In alligators, the highest densities of ISOs are found around the teeth, inside the mouth,and at the rostral margins of the mandibles and maxilla, suggesting a role in discriminating food items or determining appropriate bite force (Erickson et al, 2012). Reflecting this uncertainty regarding their functions, these receptors have also been identified as 'integumentary osmoreceptors' in respect to the body receptors found in crocodylids (Jackson and Brooks, 2007).…”
Section: Introductionmentioning
confidence: 99%